Generative AI and Sociorhetorical Views of Writing - Thieme, Katja; Amell, Brittany (Discourse and Writing/Rédactologie, 2025)
Artificial intelligence (AI) tools increasingly influence writing practices in educational contexts, yet writing studies expertise is too often sidelined in current discussions. This paper presents core insights from rhetorical genre theory and genre-based pedagogy to inform the teaching of research and writing in relation to generative AI tools. Our analysis focuses on three key concepts that are of central concern: intention, process, and trust. These terms bring relevant conceptual dynamics into the foreground—including the role that intention plays in pragmatic analysis, the way that process matters in studies of writing, and the attention that trust receives in philosophy of science. We argue that focusing on these concepts during pedagogical decision-making helps us navigate between extreme hype and grave concern about generative AI tools in the context of research writing. We draw on recent empirical research to demonstrate how longer-standing insights about intention, process, and trust relate to contemporary conditions. Our analysis contributes to ongoing conversations about the role of AI in writing pedagogy by arguing for the continued assertion of deep disciplinary expertise and its attendant pedagogies. As we show, writing studies has the potential to lead—rather than react to—these conversations.